MANIFESTAÇÕES PATOLÓGICAS EM SISTEMAS PREDIAIS HIDROSSANITÁRIOS DE EDIFÍCIOS RESIDENCIAIS - Bottega, Gabriela Schneider de Sousa; Silva Júnior, Edilson Pompeu da; Pilz, Sílvio Edmundo; Costella, Marcelo Fabiano Costella (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The plumbing systems have been indicated as one of the building systems with high levels of failures. The evaluation of these pathological manifestations and operating conditions of these systems can contribute to the continuous improvement of building performance. This study aimed to identify the failures in the plumbing systems of 16 residential buildings, where 156 apartments were analyzed. The buildings were selected in order to compose a sample of different ages and heights. The information was collected in the buildings with a checklist, which classified the pathological manifestations in leaks, clogs, odor returns, pressure, noise/vibration and manufacturing/installation defects. A total of 692 cases of failure were identified, where the main failure refers to leaks, representing 35% of the records, followed by the odor returns, representing 31%. The room with the highest incidence of failures was the bathroom, and the appliance was the toilet. In addition, it was observed that older and higher buildings had more failures than others.